Manajemen Pertahanan untuk Penanggulangan Illegal Fishing di Perairan Indonesia: Analisis Dampak dan Strategi Penanganan - Habibul Quran; Fauzia G Cempaka; Makmur Supriyatno; Hikmat Zakky al Mubaroq; Arya Dewa Nugroho (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Indonesia, as an archipelagic nation rich in marine resources, faces a serious issue related to illegal fishing. This illegal fishing practice involves foreign vessels entering Indonesian waters without permission and violating established fishing regulations. The phenomenon of illegal fishing has been a major concern for several decades due to its detrimental impact on marine resources, ecosystems, and the livelihoods of local fishermen. The purpose of this research is to provide a comprehensive understanding of the issue of illegal fishing in Indonesia. Additionally, it aims to respond to this challenge by exploring the role and strategies of defense management in addressing illegal fishing in Indonesian waters. The method used in this research is qualitative, with data collection techniques including interviews, journals, books, and documents. The results of this study indicate that illegal fishing poses a significant threat to Indonesia's marine resources, security, and the livelihoods of coastal communities. To address this issue, cooperation between the government, communities, and relevant institutions is necessary. Firm measures such as strong law enforcement, maximum maritime surveillance, and international cooperation are crucial. The role of fishermen in collaboration with law enforcement authorities is also crucial in protecting Indonesia's waters. Defense management, including maritime surveillance and the development of stringent policies, must also be considered to protect the country's security from the threat of illegal fishing.